The mediating effect of knowledge in the relationship between inventory management practices and performance: the case of micro retailing enterprises - Ahmad, Kamilah; Mohamed Zabri, Shafie (The Academy of Business and Retail Management, 2018)
The adoption of systematic inventory management practices (IMPs) is a critical success factor for businesses in a retailing industry. Nevertheless, there is lack of thorough understanding in the field of inventory management within a micro business setting. Thus, this study empirically explores the extent of IMPs in the micro retailing enterprises and the mediating effect of knowledge of IMPs on the relationship between IMPs and micro enterprises’ performance. A questionnaire was sent to a random sample of 300 Malaysian owners/managers of micro retailing enterprises and 100 completed replies were received. The study finds that the usage level of systematic IMPs is moderate among the micro retailing enterprises with evaluation of suppliers as the most frequently applied IMPs. Meanwhile, inventory management activities related to reorder point, purchasing and controlling are adopted moderately. Interestingly, this study confirms that there is a significant direct effect of IMPs on enterprise performance. The relationship is partially mediated by knowledge of inventory management. This research enhances the body of knowledge in inventory management and the firm’s performance particularly within the context of micro enterprises.